2018
DOI: 10.2337/db17-1149
|View full text |Cite
|
Sign up to set email alerts
|

MANF Is Required for the Postnatal Expansion and Maintenance of Pancreatic β-Cell Mass in Mice

Abstract: Global lack of mesencephalic astrocyte-derived neurotropic factor (MANF) leads to progressive postnatal loss of b-cell mass and insulin-dependent diabetes in mice. Similar to Manf 2/2 mice, embryonic ablation of MANF specifically from the pancreas results in diabetes. In this study, we assessed the importance of MANF for the postnatal expansion of pancreatic b-cell mass and for adult b-cell maintenance in mice. Detailed analysis of Pdx-1Cre +/2 ::Manf fl/fl mice revealed mosaic MANF expression in postnatal pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 69 publications
5
60
1
Order By: Relevance
“…We also have demonstrated that the ER stress inducer, tunicamycin, up‐regulates MANF expression in neurons and recombinant human MANF promotes the proliferation of neurons and prevents neurons from cerebral ischemia‐induced apoptosis . Meanwhile, MANF promotes the survival and proliferation of pancreatic β cells . Furthermore, MANF as an immune modulator mediates tissue repair in the mammalian retina and maintains liver metabolic homeostasis .…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…We also have demonstrated that the ER stress inducer, tunicamycin, up‐regulates MANF expression in neurons and recombinant human MANF promotes the proliferation of neurons and prevents neurons from cerebral ischemia‐induced apoptosis . Meanwhile, MANF promotes the survival and proliferation of pancreatic β cells . Furthermore, MANF as an immune modulator mediates tissue repair in the mammalian retina and maintains liver metabolic homeostasis .…”
Section: Discussionmentioning
confidence: 88%
“…(8,9) Meanwhile, MANF promotes the survival and proliferation of pancreatic β cells. (10,11) Furthermore, MANF as an immune modulator mediates tissue repair in the mammalian retina and maintains liver metabolic homeostasis. (15,31) Additionally, MANF plays key roles in facilitating the survival of cardiac cells from ischemic injury, modulating myocardial hypertrophy and heart failure as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In nematodes, a mutation in the Manf homologue was suggested to result in the gradual degeneration of dopamine neurons (Richman et al, 2018), but a recent study implicated that MANF-depleted nematodes do not after all display any dopamine phenotype (Hartman et al, 2019). We have shown that conventional MANF knock-out (KO) mice and pancreas-specific conditional KO mice develop insulin-dependent diabetes due to prolonged ER stress in pancreatic b cells, leading to loss of the b cell mass and premature death (Lindahl et al, 2014;Danilova et al, 2019a). In MANF KO mice, it was also demonstrated that MANF regulates cortical development and migration of neuronal progenitor cells (Tseng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%